Pengaruh Kompensasi dan Pengembangan Karir terhadap Kinerja Karyawan Generasi Milenial dengan Motivasi Kerja sebagai Variabel Mediasi pada Perkantoran di Jakarta - Dwirani, Novia; Aty Herawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of Compensation and Career Development on the Performance of Millennial Generation Employees Mediated by Work Motivation. The population of the study was millennial generation employees in offices in Jakarta. A sample of 100 people was taken by convenience sampling. The primary data used were responses from millennial generation employees in the Jakarta area obtained through questionnaires. The data were analyzed using PLS-based SEM. The results showed that Compensation and Career Development did not have a significant effect on Employee Performance. Compensation and Career Development have a significant effect on Work Motivation. And Compensation and Career Development do not have an indirect effect on Employee Performance mediated by Work Motivation. Keywords: Millennial Generation, Compensation, Employee Performance, Work Motivation